A New Two-Dimensional Electromagnetic Field Analysis and Loss Calculation Method for High-Frequency Applications Based on Vector Magnetic Circuit Theory - Chengbo Li; Ming Cheng; Wei Wang (Energies)
Electromagnetic field analysis and loss calculation is crucial for designing and optimizing magnetic components in high-frequency applications. The traditional method of combining eddy current field equations with hysteresis models is often used for low-frequency conditions and has complex applications due to the large number of coefficients. The loss calculation of commercial finite element software is usually in the post-processing phase, making the loss calculation and electromagnetic field analysis irrelevant. In this article, a new two-dimensional electromagnetic field analysis and loss calculation method for high-frequency applications is proposed based on vector magnetic circuit theory. The effects of eddy currents and hysteresis on the magnetic field can be considered simultaneously, and the corresponding eddy current losses and hysteresis losses can also be directly calculated. Two toroidal magnetic cores for high-frequency applications are used to verify the effectiveness and accuracy of the method proposed in this article. The analytical calculation results have higher accuracy compared to the ANSYS simulation results.